The Effectiveness of Using BBC News Video to Enhance Students’ Speaking Pronunciation and Fluency - Iksan, Muhammad Verill; Salam, Urai; Rezeki, Yanti Sri (IKIP Siliwangi, 2025)
This research explored the effectiveness of incorporating BBC News videos to enhance the speaking pronunciation and fluency of Islamic High School students. Using a pre-experimental design, the research assessed students' speaking abilities before and after exposure to BBC News. Statistical analysis revealed a significant enhancement in the students' speaking skills. The findings showed that the use of BBC News videos contributed to a noticeable, moderate enhancement in their pronunciation and fluency. This research highlights the potential of BBC News as a meaningful and engaging tool for enhancing students' speaking abilities, emphasizing its value in language learning.